Selective IgA deficiency with 18q+ and 18q– karyotypic anomalies. Issue 6 (December 1980) - Lewkonia, R M; Lin, C C; Haslam, R H
Abstract : A case is described of selective immunoglobulin A deficiency in association with an 18q+ anomaly, apparently the result of a break at 18q23 and a de novo translocation. The presentation is compared with the phenotypic and immunological features in an IgA deficient 18q– patient. The findings in these two patients suggest that gene(s) concerned with regulation of IgA synthesis are located on the distal long arm of chromosome 18 between 18q23 and qter.